Preparation method and application of Zn0. 5Cd0. 5S (at) InOOH composite material containing sulfur vacancy

By growing Zn0.5Cd0.5S nanoparticles containing sulfur vacancies on InOOH nanosheets, the Zn0.5Cd0.5S@InOOH composite material was formed, and the existing Zn0.5Cd0.5S and InOOH were solved, and the existing Zn0.5Cd0.5S and InOOH were insufficient and easy to aggregate in the field of photocatalysis, and the photocatalytic activity and efficiency were significantly improved.

CN119588378APending Publication Date: 2025-03-11HUAIYIN INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411691261.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing Zn0.5Cd0.5S and InOOH have problems such as insufficient active sites, easy aggregation, and high recombination rate of photogenerated electron/hole pairs in the field of photocatalytics, which limit their photocatalytic activity.

Method used

Zn0.5Cd0.5S nanoparticles containing sulfur vacant were grown on InOOH nanosheets by in situ growth method to form Zn0.5Cd0.5S@InOOH composite material, increasing the active site of the reaction and promoting the separation and transport of carriers.

Benefits of technology

The photocatalytic activity of the composite structure is significantly improved, and the efficiency of producing H2O2 in pure water under visible light and degrading levofloxacin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588378A_ABST
    Figure CN119588378A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of inorganic nano composite materials, and discloses a preparation method and application of a sulfur vacancy-containing Zn0. 5Cd0. 5S (at) InOOH composite material, the preparation method comprises the following steps: preparing InOOH nanosheets by a solvothermal method, adding the InOOH nanosheets into a Zn0. 5Cd0. 5S precursor solution, adding hydrazine hydrate as a reducing agent, and stirring to obtain the sulfur vacancy-containing Zn0. 5Cd0. 5S (at) InOOH composite material. The sulfur vacancy-containing Zn0. 5Cd0. 5S nanoparticle and InOOH nanosheet composite material is obtained through an in-situ hydrothermal growth method and regulation and control of experimental conditions, and the composite material is used for photocatalytic production of H2O2 and degradation of levofloxacin. According to the invention, sulfur vacancy-containing Zn0. 5Cd0. 5S nanoparticles are uniformly loaded on the surface of the InOOH nanosheet, the active sites and the specific surface area of the reaction are increased, and the agglomeration of the Zn0. 5Cd0. 5S nanoparticles is reduced; the photocatalytic activity of the composite material is greatly improved, and the composite material has a great industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of inorganic nanocomposite materials, and in particular to a Zn containing sulfur vacancies. 0.5 Cd 0.5 Preparation method and application of S@InOOH composite material, specifically, a Zn containing sulfur vacancies with high catalytic activity 0.5 Cd 0.5 Preparation method and application of S nanoparticles@InOOH nanosheet composite materials. Background Art

[0002] With the deepening of social industrialization, the problems of energy shortage and environmental pollution have become more and more serious. In order to realize the concept of sustainable development, developing a new efficient and environmentally friendly technology to solve energy shortage and environmental pollution has become a current research hotspot. Photocatalytic technology uses solar energy to excite semiconductor materials to carry out redox reactions such as hydrogen production, H2O2 production, and pollutant degradation. It is considered to be a green and environmentally friendly technology with great development potential. In photocatalytic technology, the light absorption performance of the photocatalyst, the number of active sites, and the separation of photogenerated electron pairs are the key factors affecting the photocatalytic efficiency. Therefore, the development of new low-cost, high-efficiency, and highly stable high-efficiency photocatalytic materials is the research focus of this technology.

[0003] Zn 0.5 Cd 0.5 S is a ternary sulfide solid solution composed of CdS and ZnS. It has the high light corrosion resistance of ZnS and the good visible light response performance of CdS, so it has received widespread attention in the field of photocatalysis. 0.5 Cd 0.5 S still has some inherent defects of semiconductor materials, such as insufficient active sites, easy aggregation, high recombination rate of photogenerated electron / hole pairs, etc., which seriously limits the application of Zn 0.5 Cd 0.5 Therefore, a suitable method was used to further develop Zn 0.5 Cd 0.5 It is very important to modify the ZnS to improve its photocatalytic activity. 0.5 Cd 0.5 S and construct heterojunctions with semiconductor materials matching the band gap to obtain sulfur-vacancy-containing Zn 0.5 Cd 0.5 The S-based heterojunction composite system is the most economical and effective method to enhance its photocatalytic activity and is the key research direction of this material.

[0004] InOOH is an n-type semiconductor with a wide band gap of 3.7 eV. Its high conduction band potential and low valence band potential give InOOH a high redox ability and good performance in the field of photocatalytic degradation. However, due to the wide band gap, InOOH has poor or even no response to visible light, which seriously limits the further application of InOOH in the field of photocatalysis. Recent studies have shown that by constructing a composite photocatalytic system with semiconductor materials with excellent visible light absorption performance and InOOH, its visible light response performance can be effectively improved, and the separation of photogenerated carriers can be promoted, thereby improving the photocatalytic efficiency.

[0005] Based on the above analysis, the present invention combines the advantages of the two materials to overcome their shortcomings and proposes a new type of sulfur-containing vacancy Zn 0.5 Cd 0.5 The preparation method of S@InOOH composite material was used to produce H2O2 in pure water under visible light and to degrade levofloxacin under visible light, and a high photocatalytic activity was obtained. 0.5 Cd 0.5 S nanoparticles grow on InOOH nanosheets to form sulfur-containing vacancies Zn 0.5 Cd 0.5 S@InOOH composites reduce Zn 0.5 Cd 0.5 The aggregation of S nanoparticles increases the active sites of the reaction and promotes the effective separation and transmission of charge carriers, thereby greatly improving the photocatalytic activity of the composite structure. After extensive literature research, it was found that there is currently no research on sulfur-containing vacancy Zn 0.5 Cd 0.5 There is no report on the S@InOOH composite structure, nor is there any report on the sulfur-containing Zn vacancy. 0.5 Cd 0.5 The S@InOOH composite structure was used for photocatalytic H2O2 production and degradation of levofloxacin. 0.5 Cd 0.5 S@InOOH composite structure is a new type of photocatalytic material. Summary of the invention

[0006] Purpose of the invention: To solve the problems existing in the prior art, the present invention provides a Zn containing sulfur vacancies. 0.5 Cd 0.5 The invention discloses a method for preparing a S@InOOH composite material, wherein the method first prepares InOOH nanosheets, then uses the InOOH nanosheets as a base material, adds a zinc source, a cadmium source and a sulfur source, and adds hydrazine hydrate for reduction to prepare a sulfur-containing vacancy Zn 0.5 Cd 0.5The S@InOOH nanocomposite material is used to generate H2O2 and degrade levofloxacin in pure water under visible light. The photocatalytic activity of the composite structure prepared by the invention is greatly improved.

[0007] Technical solution: In the first aspect, the present invention provides a Zn containing sulfur vacancies 0.5 Cd 0.5 The preparation method of the S@InOOH composite material comprises the following steps: Step 1, adding InCl3·4H2O to a mixed solution of deionized water and glycerol, stirring, hydrothermal reaction, cooling to room temperature, centrifuging, washing, and drying to obtain InOOH nanosheets; Step 2: Add the InOOH nanosheets to deionized water, stir ultrasonically, then add Zn(CH3COO)2·2H2O, Cd(NO3)2·4H2O and thioacetamide in sequence, continue stirring for 1-2 h, then add hydrazine hydrate, stir evenly, perform hydrothermal reaction, cool to room temperature, centrifuge, wash, and dry to obtain Zn containing sulfur vacancies. 0.5 Cd 0.5 S@InOOH composites.

[0008] Furthermore, in step 1, the usage ratio of the InCl3·4H2O to the mixed solution is 1-9 mmol: 50-200 mL.

[0009] Furthermore, in the mixed solution, the volume ratio of deionized water to glycerol is 2:1.

[0010] Furthermore, in step 1, the specific conditions of the hydrothermal reaction are: the filling ratio of the hydrothermal reactor is 50-70%, the reaction temperature is 160-220°C, and the reaction time is 10-16 h.

[0011] Furthermore, in step 2, the usage ratio of the InOOH nanosheets, Zn(CH3COO)2·2H2O, Cd(NO3)2·4H2O, thioacetamide, deionized water and hydrazine hydrate is 0.0127-0.6045 g: 1-10 mmol: 1-10 mmol: 2-20mmol: 50-300 mL: 2-20 mL.

[0012] Furthermore, in step 2, the specific conditions of the hydrothermal reaction are: the filling ratio of the hydrothermal reactor is 50-70%, the reaction temperature is 140-180°C, and the reaction time is 16-24 h.

[0013] Preferably, in step 1, the stirring time is 10-30 min; In step 2, the ultrasonic stirring time is 20-30 min.

[0014] Furthermore, the Zn containing sulfur vacancies prepared by any of the above methods 0.5 Cd 0.5 In the S@InOOH composite material, the mass ratio of InOOH ranges from 5 to 20%.

[0015] In a second aspect, the present invention provides a Zn containing sulfur vacancies prepared by any of the methods described above. 0.5 Cd 0.5 Application of S@InOOH composites to produce H2O2 in pure water under visible light.

[0016] In a third aspect, the present invention provides a Zn containing sulfur vacancies prepared by any of the methods described above. 0.5 Cd 0.5 Application of S@InOOH composite material in degradation of levofloxacin under visible light.

[0017] Beneficial effect: The present invention prepares InOOH nanosheets by a solvothermal method, and then adds the InOOH nanosheets to Zn 0.5 Cd 0.5 S precursor solution, and hydrazine hydrate was added as a reducing agent. Sulfur-containing vacancy Zn was obtained by in-situ hydrothermal growth method and controlled experimental conditions. 0.5 Cd 0.5 S nanoparticles@InOOH nanosheet composites are used for photocatalytic H2O2 production and degradation of levofloxacin. Compared with the prior art, the specific beneficial effects are as follows: 1. The present invention proposes a new type of sulfur-containing vacancy Zn 0.5 Cd 0.5 The invention discloses a S@InOOH composite material and also provides a preparation method of the novel composite material.

[0018] 2. Sulfur-containing vacancy Zn prepared by the present invention 0.5 Cd 0.5 The S@InOOH composite material presents the morphology of nanoparticles grown on nanosheets and has excellent photocatalytic activity.

[0019] 3. The present invention is the first to convert Zn containing sulfur vacancies into 0.5 Cd 0.5 The compounding of S with InOOH broadens its light absorption range, and the obtained composite material has a high light response ability, which greatly improves the utilization efficiency of solar energy.

[0020] Fourth, the present invention converts the sulfur-containing vacancy Zn 0.5 Cd 0.5 S nanoparticles and InOOH nanosheets are used to construct composite materials, which are innovative in Zn 0.5 Cd 0.5S and grown on InOOH nanosheets. The introduction of sulfur vacancies and the construction of composite structures can realize the formation of sulfur-vacancy Zn 0.5 Cd 0.5 S nanoparticles are uniformly loaded on the surface of InOOH nanosheets to form a close contact interface, which promotes the separation of photogenerated charges, increases the active sites and specific surface area of ​​the reaction, and reduces the Zn 0.5 Cd 0.5 The agglomeration of S nanoparticles; at the same time, the synergistic effect between the two greatly reduces the recombination of photogenerated carriers and promotes the separation and transfer of photogenerated electrons and holes. 0.5 Cd 0.5 S@InOOH has excellent activity in producing H2O2 and degrading levofloxacin in pure water under visible light irradiation. When the composite sample with InOOH mass ratio is 10%, the production of H2O2 can reach 2865.78 μM after irradiation under visible light for 2 h. The degradation rate of levofloxacin is 99.53% after irradiation under visible light for 40 min.

[0021] 5. The present invention uses a simple preparation process to synthesize sulfur-containing vacancy Zn 0.5 Cd 0.5 S nanoparticles@InOOH nanosheet composite materials have abundant raw material sources, simple operation process, mild and easy-to-control reaction conditions, green and simple process, no secondary pollution, and non-toxic products. It belongs to the green synthesis method. It has broad application prospects in the development of green energy and sewage treatment. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 Vs-Zn prepared in Examples 1, 3 and 5 of the present invention 0.5 Cd 0.5 XRD patterns of S@InOOH composites; Figure 2 Zn 0.5 Cd 0.5 S and Vs-Zn prepared in Example 3 0.5 Cd 0.5 EPR images of S@InOOH composites; Figure 3 Vs-Zn prepared in Example 3 of the present invention 0.5 Cd 0.5 S(a) and Vs-Zn 0.5 Cd 0.5 SEM image of S@InOOH (b) composite material; Figure 4 Vs-Zn prepared in Example 3 of the present invention 0.5 Cd 0.5 UV-vis images of S@InOOH composites; Figure 5 Vs-Zn prepared in Example 3 of the present invention 0.5 Cd 0.5 The effect of S@InOOH composite material on photocatalytic production of H2O2 and degradation of levofloxacin after four cycles of experiments under visible light; Figure 6 Vs-Zn prepared in Example 4 of the present invention 0.5 Cd 0.5 Photocurrent diagram of S@InOOH composite. DETAILED DESCRIPTION

[0023] The present invention is described in detail below in conjunction with the embodiments.

[0024] It should be noted that in the present invention, the experiment of photocatalytic H2O2 production was carried out in a top-irradiated photocatalytic reactor, using a 300 W xenon lamp as the solar light source and filtering out ultraviolet light with a λ>420 nm filter to evaluate the sulfur-containing vacancy Zn 0.5 Cd 0.5 The efficiency of H2O2 production of S@InOOH composite material in pure water. The specific steps are as follows: add 20 mg of photocatalyst to 50 mL of deionized water, stir for 10 min to make the catalyst disperse evenly, and turn on the light. Take a sample every 20 min, take the supernatant after centrifugation, use KI for color development, and then measure the absorbance of its maximum absorption wavelength (λ=350 nm) in a UV-visible spectrophotometer, and calculate the H2O2 yield based on the standard curve.

[0025] The experiment of photocatalytic degradation of levofloxacin was carried out in a top-irradiation type photocatalytic reactor, using a 300 W xenon lamp as the solar light source and a λ>420 nm filter to filter out ultraviolet light. 0.5 Cd 0.5 The degradation efficiency of levofloxacin by S@InOOH composite material. The specific steps are as follows: 70 mL (10 mg / L) of levofloxacin solution was added to the reactor, its initial absorbance was measured, and then 20 mg of sulfur-containing vacancy Zn 0.5 Cd 0.5 After the S@InOOH composite material was reacted in the dark for 30 minutes to reach the adsorption-desorption equilibrium, the light was turned on and samples were taken every 8 minutes. After centrifugation, the upper clear liquid was taken and the absorbance of the maximum absorption wavelength (λ=287 nm) was measured in a UV-visible spectrophotometer. The degradation rate of levofloxacin was calculated based on the change in absorbance before and after illumination.

[0026] Embodiment 1: This embodiment provides a Zn containing sulfur vacancies.0.5 Cd 0.5 S@InOOH composites (Vs-Zn 0.5 Cd 0.5 The preparation method of S@InOOH is as follows: 1 mmol InCl3·4H2O was weighed and added to 50 mL of a mixed solution of deionized water and glycerol (the volume ratio of deionized water to glycerol was 2:1). After stirring for 10 min, the mixture was transferred into a hydrothermal reactor with a filling degree of 50%. The reaction was carried out at 160 °C for 16 h. After the reaction was completed, the mixture was naturally cooled to room temperature, centrifuged, washed several times with deionized water and anhydrous ethanol, and vacuum dried for 12 h to obtain InOOH nanosheets.

[0027] 0.0127 g InOOH nanosheets were added to 50 mL deionized water under stirring conditions, and stirring and ultrasonication were continued for 20-30 min. The operation was repeated twice, and 1 mmol Zn(CH3COO)2·2H2O, 1 mmol Cd(NO3)2·4H2O and 2 mmol thioacetamide were added in sequence. After stirring for 1 h, 2 mL hydrazine hydrate was added. After stirring evenly, the mixture was transferred into a reactor with a filling degree of 50%. The reaction was then carried out at 140 °C for 24 h. After the reaction was completed, the precipitate was centrifuged, washed and vacuum dried for 12 h to obtain sulfur-containing vacant Zn 0.5 Cd 0.5 S@InOOH composite material, in which the mass ratio of InOOH in the composite structure is 5%.

[0028] from Figure 1 The Vs-Zn prepared in this embodiment 0.5 Cd 0.5 It can be seen from the XRD pattern of the S@InOOH composite material that the XRD pattern of the sample prepared in this embodiment is basically the same as that of the Vs-Zn 0.5 Cd 0.5 This is due to the low content of InOOH.

[0029] InOOH, Vs-Zn 0.5 Cd 0.5 S and Vs-Zn 0.5 Cd 0.5 The H2O2 production of S@InOOH composite samples under visible light irradiation for 2 h was 25.05, 292.27, and 2159.39 μM, respectively. Under visible light irradiation for 40 min, the degradation rates of levofloxacin were 5.24%, 72.46%, and 90.10%, respectively. It can be seen that the photocatalytic activity of the obtained composite samples is better than that of InOOH and Zn 0.5 Cd 0.5The S monomer has been greatly improved, especially the photocatalytic H2O2 production activity has been greatly improved.

[0030] Embodiment 2: This embodiment provides a Zn containing sulfur vacancies. 0.5 Cd 0.5 S@InOOH composites (Vs-Zn 0.5 Cd 0.5 The preparation method of S@InOOH is as follows: (1) Weigh 3 mmol InCl3·4H2O and add it to 80 mL of a mixed solution of deionized water and glycerol (the volume ratio of deionized water to glycerol is 2:1). After stirring for 15 min, transfer it into a hydrothermal reactor with a filling degree of 60%. React at 180°C for 14 h. After the reaction is completed, naturally cool to room temperature, centrifuge, wash several times with deionized water and anhydrous ethanol, and vacuum dry for 12 h to obtain InOOH nanosheets.

[0031] (2) 0.0546 g of InOOH nanosheets were added to 100 mL of deionized water under stirring conditions. Stirring and ultrasonication were continued for 20-30 min. The operation was repeated twice. 3 mmol Zn(CH3COO)2·2H2O, 3 mmol Cd(NO3)2·4H2O and 6 mmol thioacetamide were added in sequence. After stirring for 1 h, 6 mL of hydrazine hydrate was added. After stirring evenly, the mixture was transferred into a reactor with a filling degree of 60%. The reaction was then carried out at 150 °C for 22 h. After the reaction was completed, the precipitate was centrifuged, washed and vacuum dried for 12 h to obtain sulfur-containing vacant Zn 0.5 Cd 0.5 S@InOOH composite material, in which the mass ratio of InOOH in the composite material is 7%.

[0032] The Vs-Zn prepared in this embodiment 0.5 Cd 0.5 The production of H2O2 of the S@InOOH composite sample under visible light irradiation for 2 h was 2328.39 μM; the degradation rate of levofloxacin was 93.66% under visible light irradiation for 40 min.

[0033] Embodiment 3: This embodiment provides a Zn containing sulfur vacancies. 0.5 Cd 0.5 S@InOOH composites (Vs-Zn 0.5 Cd 0.5 The preparation method of S@InOOH is as follows: (1) Weigh 5 mmol InCl3·4H2O and add it to 100 mL of a mixed solution of deionized water and glycerol (the volume ratio of deionized water to glycerol is 2:1). After stirring for 20 min, transfer it into a hydrothermal reactor with a filling degree of 70% and react at 190°C for 12 h. After the reaction is completed, naturally cool it to room temperature, centrifuge it, wash it with deionized water and anhydrous ethanol several times, and vacuum dry it for 12 h to obtain InOOH nanosheets.

[0034] (2) Add 0.1343 g of InOOH nanosheets to 200 mL of deionized water under stirring, continue stirring and ultrasonication for 20-30 min, repeat the operation twice, add 5 mmol Zn(CH3COO)2·2H2O, 5 mmol Cd(NO3)2·4H2O and 10 mmol thioacetamide in turn, stir for 1 h, add 10 mL of hydrazine hydrate, stir evenly and transfer to a reactor with a filling degree of 70%. Then react at 160 °C for 20 h. After the reaction, centrifuge, wash and vacuum dry the precipitate for 12 h to obtain sulfur-containing Zn vacancy. 0.5 Cd 0.5 S@InOOH composite material, wherein the mass ratio of InOOH in the composite material is 10%.

[0035] Figure 1 The Vs-Zn prepared in this embodiment 0.5 Cd 0.5 The XRD pattern of the S@InOOH composite sample shows that the XRD pattern of the sample in this embodiment is basically the same as that of the Vs-Zn 0.5 Cd 0.5 S spectrum is consistent, but compared with Example 1, Vs-Zn 0.5 Cd 0.5 The characteristic peak intensity of S is weakened, which is due to the increase in the amount of InOOH in the composite material of this embodiment.

[0036] Figure 2 The Vs-Zn prepared in this embodiment 0.5 Cd 0.5 S and Vs-Zn 0.5 Cd 0.5 The EPR spectrum of S@InOOH composite sample shows that Vs-Zn 0.5 Cd 0.5 S and Vs-Zn 0.5 Cd 0.5 The S@InOOH composite sample has a signal peak at g=2.003, which indicates that the Vs-Zn 0.5 Cd 0.5 S and Vs-Zn0.5 Cd 0.5 There are sulfur vacancies in the S@InOOH composite structure sample.

[0037] Figure 3 The Vs-Zn prepared in this embodiment 0.5 Cd 0.5 S and Vs-Zn 0.5 Cd 0.5 SEM image of S@InOOH composite sample. It can be seen from the figure that Vs-Zn 0.5 Cd 0.5 The morphology of S is nanoparticles, Vs-Zn 0.5 Cd 0.5 The S@InOOH composite structure sample is nanoparticles grown on nanosheets, and only a small amount of InOOH flake structure can be seen. This is due to the low content of InOOH, indicating that the two have been successfully composited.

[0038] Figure 4 The Vs-Zn prepared in this embodiment 0.5 Cd 0.5 UV-vis graph of S@InOOH composite sample. It can be seen from the figure that the Vs-Zn 0.5 Cd 0.5 After S is compounded with InOOH, the visible light absorption performance of the sample is significantly improved compared with InOOH, and it has better visible light response ability.

[0039] The Vs-Zn prepared in this example 0.5 Cd 0.5 The H2O2 production of the S@InOOH composite sample under visible light irradiation for 2 h was 2865.78 μM, and the degradation rate of levofloxacin was 99.53% under visible light irradiation for 40 min.

[0040] Figure 5 The Vs-Zn prepared in this embodiment 0.5 Cd 0.5 The efficiency of the S@InOOH composite sample in producing H2O2 and degrading levofloxacin after four cycles under visible light can be seen from the figure. 0.5 Cd 0.5 The S@InOOH composite sample can still maintain a high activity after four cycles, indicating that it has high cycle stability and great prospects for industrial application.

[0041] Embodiment 4: This embodiment provides a Zn containing sulfur vacancies. 0.5 Cd 0.5 S@InOOH composites (Vs-Zn0.5 Cd 0.5 The preparation method of S@InOOH is as follows: (1) Weigh 7 mmol InCl3·4H2O and add it to 130 mL of a mixed solution of deionized water and glycerol (the volume ratio of deionized water to glycerol is 2:1). After stirring for 20 min, transfer it into a hydrothermal reactor with a filling degree of 60% and react at 200°C for 11 h. After the reaction is completed, naturally cool to room temperature, centrifuge, wash several times with deionized water and anhydrous ethanol, and vacuum dry for 12 h to obtain InOOH nanosheets.

[0042] (2) 0.2987 g of InOOH nanosheets were added to 300 mL of deionized water under stirring conditions. Stirring and ultrasonication were continued for 20-30 min. The operation was repeated twice. 7 mmol Zn(CH3COO)2·2H2O, 7 mmol Cd(NO3)2·4H2O and 14 mmol thioacetamide were added in sequence. After stirring for 1 h, 14 mL of hydrazine hydrate was added. After stirring evenly, the mixture was transferred into a reactor with a filling degree of 60%. The reaction was then carried out at 170 °C for 18 h. After the reaction was completed, the precipitate was centrifuged, washed and vacuum dried for 12 h to obtain sulfur-containing vacant Zn 0.5 Cd 0.5 S@InOOH composite material, in which the mass ratio of InOOH in the composite material is 15%.

[0043] Figure 6 The Vs-Zn prepared in this embodiment 0.5 Cd 0.5 The photocurrent diagram of S@InOOH composite sample and two monomers shows that the Vs-Zn 0.5 Cd 0.5 After S is compounded with InOOH, the photocurrent intensity generated by the composite sample under illumination conditions is significantly enhanced, indicating that the combination of the two can enhance the separation of photogenerated charges and improve the photocatalytic activity.

[0044] The Vs-Zn prepared in this embodiment 0.5 Cd 0.5 The H2O2 production of the S@InOOH composite structure sample under visible light irradiation for 2 h was 2639.42 μM, and the degradation rate of levofloxacin was 97.32% after irradiation under visible light for 40 min.

[0045] Embodiment 5: This embodiment provides a Zn containing sulfur vacancies. 0.5 Cd 0.5 S@InOOH composites (Vs-Zn 0.5 Cd0.5 The preparation method of S@InOOH is as follows: (1) Weigh 9 mmol InCl3·4H2O and add it to 200 mL of a mixed solution of deionized water and glycerol (the volume ratio of deionized water to glycerol is 2:1). After stirring for 20 min, transfer it into a hydrothermal reactor with a filling degree of 70%. React at 220°C for 10 h. After the reaction is completed, naturally cool to room temperature, centrifuge, wash with deionized water and anhydrous ethanol several times, and vacuum dry for 12 h to obtain InOOH nanosheets.

[0046] (2) 0.6045 g of InOOH nanosheets were added to 300 mL of deionized water under stirring conditions. Stirring and ultrasonication were continued for 20-30 min. The operation was repeated twice. 10 mmol Zn(CH3COO)2·2H2O, 10 mmol Cd(NO3)2·4H2O and 20 mmol thioacetamide were added in sequence. After stirring for 1 h, 20 mL of hydrazine hydrate was added. After stirring evenly, the mixture was transferred into a reactor with a filling degree of 70%. The reaction was then carried out at 180 °C for 16 h. After the reaction was completed, the precipitate was centrifuged, washed and vacuum dried for 12 h to obtain sulfur-containing Vs-Zn 0.5 Cd 0.5 S@InOOH composite material, wherein the mass ratio of InOOH in the composite material is 20%.

[0047] Figure 1 The Vs-Zn prepared in this embodiment 0.5 Cd 0.5 The XRD pattern of the S@InOOH composite sample shows that the XRD pattern of the sample in this embodiment is basically the same as that of the Vs-Zn 0.5 Cd 0.5 S spectrum is consistent, but compared with Examples 1 and 3, Vs-Zn 0.5 Cd 0.5 The intensity of the characteristic peak of S continues to weaken, which is due to the increase in the amount of InOOH.

[0048] The Vs-Zn prepared in this embodiment 0.5 Cd 0.5 The H2O2 production of the S@InOOH composite sample under visible light irradiation for 2 h was 2579.55 μM, and the degradation rate of levofloxacin was 96.83% under visible light irradiation for 40 min.

[0049] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A Zn containing sulfur vacancies 0.5 Cd 0.5 The method for preparing the S@InOOH composite material is characterized in that: The following steps are involved: Step 1, adding InCl3·4H2O to a mixed solution of deionized water and glycerol, stirring, hydrothermal reaction, cooling to room temperature, centrifuging, washing, and drying to obtain InOOH nanosheets; Step 2: Add the InOOH nanosheets to deionized water, stir ultrasonically, then add Zn(CH3COO)2·2H2O, Cd(NO3)2·4H2O and thioacetamide in sequence, continue stirring for 1-2 h, then add hydrazine hydrate, stir evenly, perform hydrothermal reaction, cool to room temperature, centrifuge, wash, and dry to obtain Zn containing sulfur vacancies. 0.5 Cd 0.5 S@InOOH composites.

2. The Zn containing sulfur vacancies according to claim 1 0.5 Cd 0.5 The preparation method of S@InOOH composite material is characterized by: In step 1, the usage ratio of the InCl3·4H2O to the mixed solution is 1-9 mmol: 50-200 mL.

3. The Zn containing sulfur vacancies according to claim 2 0.5 Cd 0.5 The preparation method of S@InOOH composite material is characterized by: In the mixed solution, the volume ratio of deionized water to glycerol is 2:

1.

4. The Zn containing sulfur vacancies according to claim 1 0.5 Cd 0.5 The preparation method of S@InOOH composite material is characterized by: In step 1, the specific conditions of the hydrothermal reaction are: the filling ratio of the hydrothermal reactor is 50-70%, the reaction temperature is 160-220°C, and the reaction time is 10-16 h.

5. The Zn containing sulfur vacancies according to claim 1 0.5 Cd 0.5 The preparation method of S@InOOH composite material is characterized by: In step 2, the usage ratio of the InOOH nanosheets, Zn(CH3COO)2·2H2O, Cd(NO3)2·4H2O, thioacetamide, deionized water and hydrazine hydrate is 0.0127-0.6045 g: 1-10 mmol: 1-10 mmol: 2-20 mmol: 50-300 mL: 2-20 mL.

6. The Zn containing sulfur vacancies according to claim 1 0.5 Cd 0.5 The preparation method of S@InOOH composite material is characterized by: In step 2, the specific conditions of the hydrothermal reaction are: the filling ratio of the hydrothermal reactor is 50-70%, the reaction temperature is 140-180°C, and the reaction time is 16-24 h.

7. The Zn containing sulfur vacancies according to claim 1 0.5 Cd 0.5 The preparation method of S@InOOH composite material is characterized by: In step 1, the stirring time is 10-30 min; In step 2, the ultrasonic stirring time is 20-30 min.

8. Zn containing sulfur vacancies prepared by the method according to any one of claims 1 to 7 0.5 Cd 0.5 S@InOOH composite material, characterized by: The sulfur vacancy-containing Zn 0.5 Cd 0.5 In the S@InOOH composite material, the mass ratio of InOOH ranges from 5 to 20%.

9. Zn containing sulfur vacancies prepared by the method according to any one of claims 1 to 7 0.5 Cd 0.5 Application of S@InOOH composites to produce H2O2 in pure water under visible light.

10. Zn containing sulfur vacancies prepared by the method according to any one of claims 1 to 7 0.5 Cd 0.5 Application of S@InOOH composite material in degradation of levofloxacin under visible light.